Critical Failure: A Card Game to Support the Learning of Non-Functional Testing: Exploring Software Quality Attributes through Competition and Engagement - S. e Oliveira, Andre L.; Nascimento, Matheus; Filho, Antonio; Nascimento, Ana Cecilia; Ramos, Erik Freire; Silva, Christopher A. T. da; Aguiar, Yuska Paola Costa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
Teaching non-functional testing and software quality attributes presents persistent challenges due to the abstract and theoretical nature of the content. To address this, we developed Critical Failure, a card game designed to support learning through playful competition and active engagement. Inspired by poker mechanics and adapted for educational use, the game encourages players to evaluate and critique each other’s hands as software systems, simulating the evaluation of quality attributes such as performance, usability, and security. The game was created as part of a Software Testing course to offer a more interactive alternative to traditional lectures. The game was played by a group of 17 students who provided highly positive feedback on its clarity, engagement, and educational value. Suggestions for improvement were incorporated into the final version, refining both gameplay balance and alignment with course content. The activity demonstrated strong potential as a didactic tool, helping students not only recognize various non-functional requirements but also understand how they interact and impact the testing process. This article presents the design of the game and reports on its initial classroom use as an exploratory activity, intended to gather impressions, refine mechanics, and assess its potential as a complementary tool for teaching non-functional testing concepts.